O ensino de probabilidade no 8º ano por meio de atividades experimentais - ALENCAR, Gabriela Serras de (2022)
The teaching of mathematics has been considered difficult and complex, in addition, it has been seen as frowned upon and boring by students. It is no different with the content of probability, this topic is usually feared by most teachers and, most of the time, it is forgotten or poorly worked in the classroom, so that it is seen as irritating and difficult by most students. The main objective of this work is to demonstrate the importance of teaching probability through experimental activities, for students of the 8th year of elementary school II. It addresses some aspects of teaching mathematics in the classroom and mainly resorts to efficient methodologies currently known as mathematical trends. The resource of materials such as games and the problem solving method are mainly used to try to motivate and challenge students to a search for knowledge and open new options for teachers to work in the classroom in a way that can value teaching. of probability.